Stability problems of steel‐concrete members composed of high‐strength materials - Kala, Zdeněk; Puklický, Libor; Omishore, Abayomi; Karmazínová, Marcela; Melcher, Jindřich (Journal of Civil Engineering and Management, 2010)
The presented paper deals with the stochastic analysis of the ultimate limit states of steel‐concrete building members. The load carrying capacity of steel‐concrete columns, comprising of steel profiles encased in high strength concrete, in compression is analyzed. The first part of the paper lists assumptions for the determination of the theoretical load carrying capacity of the column. Principles of elasticity and plasticity are used to determine stresses in the concrete and steel sections. Statistical characteristics of input material and geometrical imperfections are listed. Results of the theoretical analysis are then compared with results of experimental research. Statistical characteristics of obtained results of the theoretical analysis were verified using statistical characteristics obtained from experimental research. Numerical simulation LHS and Monte Carlo methods, which take into account the influences of variability of input imperfections, were employed. The influence of the utilization of the plastic reserve in the determination of the load carrying capacity of the analysed strut is shown. The influence of the initial geometric imperfections of initial strut curvature on the load carrying capacity is also presented. First Published Online: 10 Feb 2011